Laughing at Patriarchy: Satire, Gender, and Survival in Parini Shroff’s The Bandit Queens - Shradhananda Dash Madhab; Ananda Sethi Ananda (English Language and Literature in Education Journal, 2026)
Abstract  Parini Shroff’s 2023 debut novel, The Bandit Queens, uses dark comedy and satirical inversion to dissect the mechanisms of patriarchal oppression in a rural Indian village. This paper argues that Shroff employs satire not merely for comedic effect but as a sophisticated literary weapon and a crucial survival strategy for her marginalised female characters. By reappropriating the figure of the "bandit queen"—a trope historically laden with both fear and fascination—Shroff creates a narrative where gossip, rumour, and the performance of monstrousness become tools of subversion. The novel centres on Geeta, a woman wrongly believed to have murdered her husband, who finds unexpected power and community in this false reputation. This analysis examines how Shroff’s satire targets the absurdities and violences of entrenched patriarchy, from domestic abuse and economic disenfranchisement to the pervasive social scrutiny of women. Furthermore, it explores the novel’s complex portrayal of female solidarity, which is not idealised but presented as a messy, pragmatic, and often contentious alliance forged in necessity. Through close reading and theoretical frameworks drawn from feminist and postcolonial scholarship, this paper contends that The Bandit Queens exemplifies a new mode of feminist satire, one that leverages laughter to dismantle oppressive structures, envision alternative forms of justice, and ultimately, narrate a story of collective resilience and liberation.